Influences of moisture content and compressive loading speed on the mechanical properties of maize grain orientations - Chandio, Farman Ali; Li, Yaoming; Ma, Zheng; Ahmad, Fiaz; Syed, Tabinda Naz; Shaikh, Sher Ali; Tunio, Mazahr Hussian (International Journal of Agricultural and Biological Engineering, 2021)
Determination of the mechanical properties (rupture force, deformation, hardness, and toughness) of maize grain could be a significant concern for designing the harvester, thresher, and handling, processing, and storage equipment. Thus, the present research was conducted to assess the vertical and lateral rupture force, deformation, hardness, and toughness of maize grain (Beijing Denong, Lianchuang, Suyu 20, Liyu 88 and Suyu 29) influenced by different moisture contents (11.2%, 17.5%, and 21.3%) and compressive loading speeds (5, 10, 15, 20, and 25 mm/min, respectively). Besides, the mean length, width, thickness, geometric mean diameter, equivalent diameter, arithmetic diameter, sphericity, grain volume, surface area, and aspect ratio of the selected varieties were measured. The results showed that the highest length, width, thickness and sphericity, grain volume, surface area, and aspect ratio were obtained at moisture of 21.3%, whereas the lowest was at 11.2%. Moreover, it was observed that as increasing the loading speed from 5 to 25 mm/min, the vertical and lateral rupture forces decreased. However, as increasing moisture contents from 11.2% to 21.3%, the vertical and lateral rupture forces, hardness, and toughness decreased noticeably. Furthermore, the maximum correlation (R2=0.9957) between rupture force and loading speed was found for Liyu 88 at moisture of 17.5% and minimum correlation (R2=0.7002) was found for Suyu 29 at moisture of 11.2%. Moreover, the highest lateral and vertical rupture force was noticed (p<0.05) at a loading speed of 5 mm/min. Based on the experimentally obtained results, it was concluded that the properties of maize grain evaluated were relevant to the design of planter, harvesters, thrashers, and processing machine. Keywords: maize grain, moisture content, compressive loading speeds, mechanical properties, orientation DOI: 10.25165/j.ijabe.20211404.6072 Citation: Chandio F A, Li Y M, Ma Z, Ahmad F, Syed T N, Shaikh S A, et al. Influences of moisture content and compressive loading speed on the mechanical properties of maize grain orientations. Int J Agric & Biol Eng, 2021; 14(4): 41–49.